(untitled) (MAUSAM, 1964)
An electronic thermometer designed by the author for remote indicating application meteorology uses p-n-p germanium junction transistor as the sensor element and a D.C. voltmeter Calibrated terms of temperature as the indicator. The principle of its operation, scope and imitations are described in this paper. A wet and dry-bulb thermometer system consisting of two transistor sensors is also described.